C-Reactive Protein Level at Time of Discharge Is Not Predictive of Risk of Reoperation or Readmission in Children With Septic Arthritis - Bouchard, Maryse; Shefelbine, Lara; Bompadre, Viviana (Frontiers in Surgery, 2019)
Purpose: C-reactive protein (CRP) level is used at our tertiary pediatric hospital in the diagnosis, management, and discharge evaluation of patients with septic arthritis. The purpose of this study was to evaluate the efficacy of a discharge criterion of CRP <2.0 mg/dL for patients with septic arthritis in preventing reoperation and readmission. We also aimed to identify other risk factors of treatment failure. Methods: Patients diagnosed with septic arthritis between January 1, 2007 and December 31, 2017 were identified with ICD 9/10 and related CPT codes. Systematic chart reviews were performed to obtain demographic data, infection characteristics, and treatment details. Bivariate tests of associations between potential risk factors and readmission and reoperation were performed. Quantitative variables were analyzed using Mann-Whitney tests and categorical variables were analyzed using Chi-square tests. Results: One hundred and eighty-three children with septic arthritis were included in the study. Seven (3.8%) were readmitted after hospital discharge for further management, including six who required reoperation. Mean CRP at discharge for single-admission patients was 1.71 mg/dL (+/- 1.07) and 1.96 mg/dL (+/- 1.19) for the readmission group (p=0.664). Forty-eight children (25.9%) had CRP values greater than the recommended 2.0 mg/dL at discharge. Only three of these patients (6.2%) were later readmitted. The only common variable of the readmitted children was an antibiotic-resistant or atypical causative bacteria. Conclusions: CRP levels are useful in monitoring treatment efficacy of septic arthritis in children but are not reliable as a discharge criterion to prevent readmission or reoperation. We recommend determining discharge readiness on the basis of clinical improvement and down-trending CRP values. There was a higher risk of readmission in children with an antibiotic-resistant or atypical causative bacteria. Close monitoring of these patients and those with negative cultures at time of discharge is suggested to identify signs of persistent infection.